مزايا شعر عنترة بن شداد والأفکار الإسلامية فيه: The characteristics of Antâra’s poetry and his Islamic thoughts (Al-Qamar, 2021)
In this article, the poetry of Antâra is included which has a great similarity with Islamic thoughts. Antîra bin Shaddad is a poet of ignorant era. But his poetic thoughts were considered the spirit of Islam that the holy prophet has preached and made it a principle of his entire life.  Antâra rejected the evil habits and bad characters and he insisted on Kindness, safety of life and property, respect of women and ethics in his poetry, which were described and Preached in Hadîth later. For example, the Holy Prophet says, that there is no superiority of black on white or of white over black. Similarly, there is no superiority of Arabic people over non-Arabic people but as human beings, all are equal. Antâra has also discussed this issue in his poetry that there is no superiority, but that man will be considered best who has good character and does good deeds. Antâra bin shâddad Stressed on self-respect. He says if someone gives me the water of life in an insulting way, I don’t need it because it makes my life hell. Antâra wants that every person should stay in this world with respect. Therefore, he also stressed generosity, because it is fruitful for others. Antara bin shaddad considered modesty as a necessary element of respect in the society. Antara bin Shaddad, s thoughts about death are like Islamic philosophy. He said in his poetry that everyone had to face the death because it was inevitable. Qûran also gives us the same philosophy. In short, a lot of poetry of Antara is Islamic ideology that is the reason that Mohammad (S.W.A) wished to meet Antâra. Antâra bin shaddad says that all human beings have equal self-esteem. He also describes the same philosophy of life which the Holy Prophet preached.
Keywords: Antâra bin Shâddad; Reflection; Similarities; Islamic; thoughts